Integrating ICT to Enhance School Functioning: A Case Study of Lutheran Schools in Fianarantsoa, Madagascar - Rakotomalalaridio Antsa Sahala; Ratiarimananjatovo Narindra; Razakatiana Andriamampitasoa Daniel José; Ratsimandisa Haritiana Zo; Rakotomalala Nivomboahangy Razanamiarisoa; Razafindrazanakolona Andrianjafimanjato Daniel; Ratsimbazafy; Robijaona Rahelivololoniaina Baholy (Matondang Journal, 2025)
This study investigates the integration of Information and Communication Technologies (ICTs) in Lutheran schools in Fianarantsoa, Madagascar. Through classroom observations, interviews with teachers and school principals, and document analysis, the study examines the current level of ICT integration and identifies key challenges and opportunities. Findings reveal significant discrepancies between established best practices and actual classroom practices in areas such as administrative organization, pedagogical approaches, and didactic methods. Notably, teacher training in ICT integration is crucial, requiring a structured approach that addresses pedagogical skills, resource utilization, and the development of student-centered learning environments. The study emphasizes the importance of leveraging ICTs to enhance teaching and learning, foster student engagement, and improve overall educational outcomes in the context of Lutheran schools in Fianarantsoa.